The Tourism Sector: A bright light in Zimbabwe`s depressed economic environment - Zhou, Zibanai (Africa Journals, 2021)
This paper aims to respond to a knowledge gap on an important macro- economic question that has ignited inconclusive debates among investors and policy makers on whether or not tourism can lead to economic development in transitioning economies. The common narrative that tourism is a magic bullet for economic transformation consistently cited by tourism pundits is typically based on speculative and generalised country specific contextual variables. This research paper aims to examine the commonly discussed socio-economic benefits of tourism to provide a richer comprehension of these benefits in the various tourist destination contexts. The study adopted a descriptive-qualitative method through desk research and in-depth interviews with government, local residents, 200 registered local tourism operators and industry expert opinion leaders to probe the economic system-wide impact of tourism in Zimbabwe. Quotations from participants were used to highlight core themes relevant to critical theories of tourism and economic growth. The research results show that the tourism sector contributes over $500 million into the national economy; supports in excess of 200 000 employees directly; favours massive infrastructural developments; supports conservation of resources, and spruces the image of the country. By examining the economic systemwide impacts spawned by the tourism phenomenon, this paper expands the conversation about tourism and economic growth of which very little has been documented in transitioning economies. Hence, this study, which focuses on Zimbabwe aims to fill this knowledge gap. It is envisaged that the implementation of strategies proffered herein will cause a seismic shift in Zimbabwe`s tourism landscape and economic fortunes.